Impact of Culture on Human Resource Management Practices in Saudi Arabia Multinational Corporation in China - Maghrab, Zainab (2010)
There area of research in terms of culture for this project would be on addressing the impact of culture on the human resource management (HRM) function of the Saudi Arabian multinational companies in China. This report is focused on examining these issues and then making appropriate recommendations as deemed to be appropriate.